Detection of Yersinia pestis in Canine and Feline Companion Animals in the United States - Christina Weller; Dr. Ashley Malmlov; Dr. Josh Daniels; Dr. Paula Schaffer; Dr Kristy Pabilonia (International Journal of Infectious Diseases)
Introduction: Yersinia pestis, the causative agent of plague, affects numerous wildlife reservoir species in the United States (US), such as prairie dogs, rodents and squirrels, and is maintained in a sylvatic cycle involving mammals and their fleas. Y. pestis can be transmitted to companion animals through flea bites or direct contact with or consumption of infected wild mammals. Felids, including domestic cats, are highly susceptible and their clinical presentation is easily recognizable and includes enlarged lymph nodes and unexplained high fever. Canids, including domestic dogs, have historically demonstrated relative resistance to infection, although publications have documented 7 clinical domestic dog cases in the US and 1 in China in the past 30 years. Additionally, retrospective studies have documented evidence of potential previously undiagnosed domestic dog cases in the US. Veterinarians may not include plague as a differential diagnosis in a clinically ill dog due to lack of recognition of disease presentation and lack of awareness of the potential for infection in domestic dogs. Importantly, humans can contract severe, life-threatening disease from infected domestic animals. Methods: Diagnostic testing records from 2010 to 2023 were evaluated to understand the scope of Y. pestis in companion animals and evaluate detection rates, case history, clinical presentation, and associated human illness. Results: During this period, we received 259 domestic feline and 298 domestic canine samples for testing from across the US. Of these, Y. pestis was detected in 20 cats (7.72%) and 4 dogs (1.34%). All positive cases were detected in companion animals residing in Colorado, a geographic region known to have a high prevalence of plague in wildlife reservoir species. For cases where multiple sample types were submitted, Y. pestis was detected in almost all or all samples, demonstrating the systemic spread of the bacteria. Common sample types included respiratory swabs, whole blood and tissues, including lymph node. Positive feline cases typically reported a case history of fever and lymphadenopathy. Positive canine cases presented with high fever and severe pneumonic disease and hemoptysis and were the first reported detections in severely ill domestic dogs in the US. At least one of the positive cases in a companion dog was known to be associated with clinical illness in one or more humans. Discussion: Review of Y. pestis diagnostic submissions and test results provides data that can be utilized to educate veterinarians, medical providers and public health officials on clinical presentation, disease prevalence, geographical risk, and zoonotic potential, and highlights the importance of collaborative communications between these healthcare workers. Conclusion: Detection of Y. pestis in companion animals suggests that additional surveillance may be important in preventing zoonosis.